PHYSICAL, CHEMICAL AND BIOLOGICAL HAZARDS TO PORT WORKERS AND THEIR POTENTIAL TO CAUSE RESPIRATORY DISORDERS - Tatiele Roehrs Gelati; Clarice Alves Bonow; Andréia Martins do Couto; Marlise Capa Verde de Almeida; Daniela Inês Thier Roloff; Marta Regina Cezar-Vaz (Universidade Federal do Paraná, 2017)
The present study aimed to identify the sources of chemical, physical and biological hazards to which temporary port workers are exposed in the work environment, which may cause respiratory disorders. Quantitative and exploratory study with direct nonparticipant observation of workers from a maritime port in Southern Brazil. Data was collected from July to December 2014, and 87 observations of 66 workers were made. Descriptive statistics was performed with absolute and relative frequencies (percentage). The predominant sources of physical hazards were cold, moisture and non-ionizing radiation. The sources of chemical hazard were associated with the handling of grains, fertilizers and combustible gases, and the biological hazard observed was the presence of pigeons. Port workers are exposed to occupational hazards that pose respiratory health risks, depending on the type of cargo, activities and workplace.